OBTAINING AND PHYTOCHEMICAL STUDY OF EXTRACTS OF Annona muricata (GUANÁBANA) INDUCED BY ITS CORROSION INHIBITING EFFECT - Vergara Sotomayor, Abel (2018)
In the present study, the ethanolic and aqueous extracts of the leaves of Annona muricata L. were obtained. The extraction conditions were established from the total soluble solids content and the corrosion inhibiting effect obtained from the polarization resistance, Rp (Ω • cm2), of the steel 1008, in a 1 Molar solution of HCl in the absence and presence of the inhibitor extract. The extracts with greater corrosion inhibiting effect were characterized by phytochemical screening, quantification of total phenols, alkaloids, flavonoids and antioxidant activity (DPPH). The ethanolic extract had a 1.5 times greater corrosion inhibiting effect than the aqueous extract. The phytochemical screening established that both extracts contain a wide variety of secondary metabolites, such as phenols, alkaloids, flavonoids, tannins and sesquiterpenoid lactones. Among the studied extracts, the ethanolic extract had the highest content in total phenols (582.99 and 523.34 μg EAG / mL EE), alkaloids (3.76 and 1.52 % lupanin) and flavonoids (1.14 and 0.76 mg quercetin/mL of extract), but the lowest antioxidant activity (91.45 and 94.93 % of DPPH). The images obtained by SEM and the EDS analysis for the steel exposed to the acid solution in the absence and presence of the inhibitor extract showed its protective against corrosion.